Whole-genome analysis suggesting probiotic potential and safety properties of Pediococcus pentosaceus DSPZPP1, a promising LAB strain isolated from traditional fermented sausages of the Basilicata region (Southern Italy) - Tathode, Madhura S.; Bonomo, Maria Grazia; Zappavigna, Silvia; Mang, Stefania Mirela; Bocchetti, Marco; Camele, Ippolito; Caraglia, Michele; Salzano, Giovanni (Frontiers in Microbiology, 2024)
Many lactic acid bacteria (LAB) strains are currently gaining attention in the food industry and in various biological applications because of their harmless and functional properties. In view of the increasing demand for safe food from consumers, expanded research focusing on potential probiotic bacteria is beneficial. Therefore, we aim to characterize Pediococcus pentosaceus DSPZPP1, a LAB strain isolated from traditional fermented sausages from the Basilicata region of Southern Italy. In this study, we analysed the whole genome of P. pentosaceus DSPZPP1 strain and performed in silico characterisation to evaluate its applicability for probiotics and use in food industry. The whole genome assembly and functional annotations revealed many interesting characteristics of DSPZPP1 strain. Sequencing raw reads were assembled into a draft genome of size 1,891,398 bp, with a G + C content of 37.3%. Functional annotation identified 1930 protein-encoding genes and 58 RNAs including tRNA, tmRNA, and 16s, 23s, 5s rRNAs. Analysis shows presence of genes that encodes water-soluble B-group vitamins such as biotin, folate, coenzyme A, and riboflavin. Furthermore, analysis revealed DSPZPP1 strain has capability to synthesize class II bacteriocin, Penocin A, adding importance to the food industry for bio-enriched food. The DSPZPP1 genome does not show presence of plasmids, and no genes associated with antimicrobial resistance and virulence were found. In addition, two intact bacteriophages were identified. Importantly, the lowest probability value in pathogenicity analysis indicate that this strain is non-pathogenic to humans. 16s rRNA-based phylogenetic analysis and comparative analysis based on ANI and Tetra reveals DSPZPP1 strain shares closest evolutionary relationship with P. pentosaceus DSM 20336 and other Pediococcus strains. Analysis of Carbohydrate Active Enzymes (CAZymes) identified Glycosyl transferases (GT) as a main class of enzymes followed by Glycoside hydrolases (GH). Our study reveals several interesting characteristics of isolated DSPZPP1 strain from fermented Italian sausages, suggesting its potential use as a promising probiotic candidate, and making it more appropriate for selection as a future additive in bio-preservation.